2008
DOI: 10.1289/ehp.11537
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A at Environmentally Relevant Doses Inhibits Adiponectin Release from Human Adipose Tissue Explants and Adipocytes

Abstract: BackgroundThe incidence of obesity has risen dramatically over the last few decades. This epidemic may be affected by exposure to xenobiotic chemicals. Bisphenol A (BPA), an endocrine disruptor, is detectable at nanomolar levels in human serum worldwide. Adiponectin is an adipocyte-specific hormone that increases insulin sensitivity and reduces tissue inflammation. Thus, any factor that suppresses adiponectin release could lead to insulin resistance and increased susceptibility to obesity-associated diseases.O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
273
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(297 citation statements)
references
References 37 publications
18
273
2
4
Order By: Relevance
“…In adult humans, however, epidemiological evidence exist that point to BPA as an important environmental risk factor in the development of type 2 diabetes (Lang et al, 2008). In addition, there are causal links between BPA exposure and insulin resistance (Alonso-Magdalena et al, 2006), alteration of insulin biosynthesis and secretion in β-cells in adult male mice and decrease of adiponectin in human adipocytes (Hugo et al, 2008). Insulin resistance and decrease of adiponectin should contribute to the development of type 2 diabetes, especially in subjects with a genetic susceptibility to β-cell failure.…”
Section: Discussionmentioning
confidence: 99%
“…In adult humans, however, epidemiological evidence exist that point to BPA as an important environmental risk factor in the development of type 2 diabetes (Lang et al, 2008). In addition, there are causal links between BPA exposure and insulin resistance (Alonso-Magdalena et al, 2006), alteration of insulin biosynthesis and secretion in β-cells in adult male mice and decrease of adiponectin in human adipocytes (Hugo et al, 2008). Insulin resistance and decrease of adiponectin should contribute to the development of type 2 diabetes, especially in subjects with a genetic susceptibility to β-cell failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, results from several studies have revealed that BPA can stimulate rapid cellular responses at very low concentrations, below the levels where BPA is expected to bind to the classical nuclear ERs (Welshons et al 2006). BPA has also been shown to bind to a membrane-associated ER and produce non-genomic steroid actions (Wetherill et al 2007) with the same efficacy and potency as estradiol (Alonso-Magdalena et al 2005;Hugo et al 2008). Whatever the mechanism, BPA can cause effects in animal models at doses in the range of human exposures, indicating that it can act at lower doses than predicted from some in vitro and in vivo assays (Richter et al 2007;Vandenberg et al 2007;vom Saal et al 2007;Wetherill et al 2007).…”
mentioning
confidence: 99%
“…To this end, we performed transcriptional profiling by exposing human in vitrodifferentiated mature adipocytes obtained from male non-obese, prepubertal children to E 2 . Adipocytes were treated with 1 nM E 2 , a concentration that was previously reported as the minimum dose needed to achieve BPAsimilar effects on adiponectin suppression in adipose tissue from human breast explants (Hugo et al 2008). This concentration is also known to activate in vitro ERs .…”
Section: Gene Profiling and Pathways Analysismentioning
confidence: 99%
“…Preadipocytes from eight non-obese, prepubertal children were in vitro differentiated into mature adipocytes as described above and were treated in a time-course analysis (12, 24, and 48 h) with different environmental doses of BPA exposure (1, 10, and 100 nM) (Hugo et al 2008). BPA concentrations were chosen by taking into account previous studies that described the concentrations that were able to affect metabolic homeostasis (Hugo et al 2008), the BPA ranges found in adult and fetal serum (Welshons et al 2006), and the range of BPA concentrations detected by our group in children's urine (Nicolucci et al 2013).…”
Section: Validation Of Gene Expression and Bpa Effects On Selected Genesmentioning
confidence: 99%
See 1 more Smart Citation